2007
DOI: 10.1093/nar/gkm962
|View full text |Cite
|
Sign up to set email alerts
|

The hepatitis C sequence database in Los Alamos

Abstract: The hepatitis C virus (HCV) is a significant public health threat worldwide. The virus is highly variable and evolves rapidly, making it an elusive target for the immune system and for vaccine and drug design. Presently, ∼50 000 HCV sequences have been published. A central website that provides annotated sequences and analysis tools will be helpful to HCV scientists worldwide. The HCV sequence database collects and annotates sequence data, and provides them to the public via a website that contains a user-frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
142
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 14 publications
1
142
0
Order By: Relevance
“…In contrast, two or three mutations are required for genotype 2a, 4a, and 6a viruses. This holds true for other published isolates of these subtypes (66). Such differences likely translate into clinical differences, and higher treatment failure rates were observed for genotype 1a viruses, which require one nucleotide change for R155K, than for genotype 1b viruses, which require two changes (4).…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, two or three mutations are required for genotype 2a, 4a, and 6a viruses. This holds true for other published isolates of these subtypes (66). Such differences likely translate into clinical differences, and higher treatment failure rates were observed for genotype 1a viruses, which require one nucleotide change for R155K, than for genotype 1b viruses, which require two changes (4).…”
Section: Discussionmentioning
confidence: 86%
“…This lack of sensitivity to telaprevir and boceprevir might be explained by V170, found for the majority of genotype 4a isolates and associated with PI resistance (alignment of 17 genotype 4a NS3P sequences deposited in the European HCV database, generated July 2015 [55], and the 2008 Web alignment from the Los Alamos HCV database [56]) (5,9). The comparatively low sensitivity of original genotype 3a recombinants to all PIs might be explained by Q168, conserved for genotype 3a, and V170, found in 3a(S52) (alignment of 28 genotype 3a NS3P sequences deposited in the European HCV database, generated July 2015 [55], and the 2008 Web alignment from the Los Alamos HCV database [56]) (5,9,10). The testing of additional genotype 2a and 3a isolates suggested that there were no major EC 50 differences for different isolates of the same genotype (Table 1; also see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All available HCV genotype 1b NS3 sequences were retrieved from the public HCV sequence database (13). Identical sequences and sequences of unknown origin were removed, and additional sequences obtained in Germany and China were added and aligned by using Geneious 7.0.6 (Biomatters, Auckland, New Zealand).…”
Section: Expansion Of Peptide-specific Cd8mentioning
confidence: 99%